CISTERN - AN ALTERNATIVE TO ECONOMIC AND ENVIRONMENTAL DEVELOPMENT IN RURAL AND URBAN AREAS - Monteiro, Tania Thais; Polli, Henrique Quero (Revista Interface Tecnológica, 2021)
The lack of drinking water is an alarming problem that increases with time. Due to this factor, the present work aims to demonstrate the advantages and benefits brought about by the use of cisterns, as a sustainable and economical alternative way for the storage and reuse of rainwater, as a sustainable and economical way, developing projects so that people who have limitations to water access, have more water availability mainly for domestic tasks, thus avoiding the use of drinking water to carry out these tasks. Research methodology in scientific articles was used to identify the benefits of using the Cistern. We concluded through research in the specialized literature, that the use of cisterns is fundamental to the socioeconomic development of communities of populations with vulnerability due to the low access to water resources and fundamental to the preservation of water resources due to the decrease in the use of treated water for purposes less noble.
Keywords: Reuse; Rain; Hydraulic